2022
DOI: 10.3389/fimmu.2022.935367
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Zap70 by Lck Forms the Mechanistic Basis of Differential Expression in CD4 and CD8 T Cells

Abstract: Lck and Zap70, two non-receptor tyrosine kinases, play a crucial role in the regulation of membrane proximal TCR signaling critical for thymic selection, CD4/CD8 lineage choice and mature T cell function. Signal initiation upon TCR/CD3 and peptide/MHC interaction induces Lck-mediated phosphorylation of CD3 ITAMs. This is necessary for Zap70 recruitment and its phosphorylation by Lck leading to full Zap70 activation. In its native state Zap70 maintains a closed conformation creating an auto-inhibitory loop, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…However, vitamin C is also involved in the selection of functional TCRαβ pairs after the β-selection stage [ 32 ]. Reports showed that ascorbic acid supplementation increases zeta-chain-associated protein kinase 70 (ZAP70) expression, a kinase crucially involved in T cell signaling and the development of CD8 single-positive (SP) cells [ 32 , 36 ]. Moreover, vitamin C supplementation along with inhibition of DNA and histone methylation promote the transition from DN to DP thymocytes [ 32 ].…”
Section: Impact Of Vitamin C On the Development Of T Cellsmentioning
confidence: 99%
“…However, vitamin C is also involved in the selection of functional TCRαβ pairs after the β-selection stage [ 32 ]. Reports showed that ascorbic acid supplementation increases zeta-chain-associated protein kinase 70 (ZAP70) expression, a kinase crucially involved in T cell signaling and the development of CD8 single-positive (SP) cells [ 32 , 36 ]. Moreover, vitamin C supplementation along with inhibition of DNA and histone methylation promote the transition from DN to DP thymocytes [ 32 ].…”
Section: Impact Of Vitamin C On the Development Of T Cellsmentioning
confidence: 99%